Knowledge, Attitudes, and Practices Regarding Pediatric Asthma Management: A Study Among Healthcare Professionals in Four Tertiary Hospitals of India - Tewatia, Srishti; Sharma, Parnika; Sharma, Yash; Kaushik, Kanak; Yadav, Khushi; Jalandhara, Sanjeevani; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Pediatric asthma is a major public health concern in India, requiring effective knowledge, positive attitudes, and appropriate practices among healthcare providers. Objective: To assess knowledge, attitudes, and practices (KAP) regarding pediatric asthma management among MBBS students/interns, BDS students, and paramedical staff in tertiary hospitals. Methods: A cross-sectional questionnaire-based study was conducted among 250 participants (100 MBBS students/interns, 50 BDS students, and 100 paramedical staff) across four tertiary hospitals in India. Results: MBBS students demonstrated higher knowledge scores (78%) compared to BDS students (62%) and paramedical staff (55%). Positive attitudes toward asthma education and inhaler use were reported by 85% of MBBS students, 70% of BDS students, and 60% of paramedical staff. However, gaps in practice were noted, particularly in inhaler technique demonstration (only 40% of paramedical staff and 55% of MBBS students performed correctly). Conclusion: While knowledge and attitudes were generally favorable, practices remain suboptimal. Structured training programs and interprofessional workshops are recommended to improve pediatric asthma management.